INNOVATION STRATEGY IN HUMAN RESOURCES MANAGEMENT TO INCREASE ORGANIZATIONAL EFFECTIVINESS - Mulia Sosiady; Ermansyah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Innovation in human resource management (HR) is a key factor in increasing organizational effectiveness in the digital era and increasingly fierce global competition. This research aims to analyze innovation strategies in HR management and their impact on organizational effectiveness through a literature review approach. Various innovations in recruitment, training, performance management and employee welfare have been proven to increase employee productivity, engagement and job satisfaction. Research findings show that digitalization in recruitment, the application of technology-based learning such as e-learning and virtual reality (VR), as well as data-based performance management systems help organizations optimize workforce management. Additionally, innovations in employee wellbeing, such as flexible work policies and financial wellbeing programs, contribute to improving work-life balance. However, implementing this innovation faces challenges such as resistance to change, technological limitations, and a lack of digital skills among employees. This research contributes to the field of HR management by offering insight into innovative strategies that can be implemented to increase organizational effectiveness. Organizations that want to remain competitive need to adopt HR innovation strategically, with the support of strong leadership and investment in employee skills development. Thus, innovation in HR management can be a key driver for organizational sustainability and competitiveness in the future.